PESIMISME IBN JAWZĪ TERHADAP POLARISASI KEAGAMAAN DALAM ISLAM - Fail, Moh; Nasir, Afif Ainun; Aziz, Ahmad Amirudin (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2021)
Conflicts in the Islamic world are primarily caused by disagreements between scholars’ views and thoughts. This divergence of opinion stems from scholars’ interpretations of the Qur’an and Hadith, which serve as a guide to life and religion for Muslims. This condition has existed since the Prophet Muhammad’s demise, specifically during the time of the Companions. Until then, it occurred on a continuous basis until now. This divergence in thought and perception eventually results in different forms of religious polarization, with the ulama separated or divided into various classes. The Muslims were then separated and divided into sects as a result of this situation. As mentioned by Ibn al-Jawzī, the disputes that erupted in the Islamic world and eventually resulted in religious polarization arose as a result of divergent interpretations of religious scriptures, which were bolstered by a sense of community or group fanaticism. Additionally, unscrupulous scholars’ variations caused the ulama to break into two classes or attitudes. Among them are the ulama who really care for Islam. The second category is different scholars, or scholars who are more concerned with their own expertise and with the interests and benefits of their own community than with the interests and benefits of the general public.